The Choroid Plexus Functions as a Niche for T-Cell Stimulation Within the Central Nervous System - Strominger, Itai; Elyahu, Yehezqel; Berner, Omer; Reckhow, Jensen; Mittal, Kritika; Nemirovsky, Anna; Monsonego, Alon (Frontiers in Immunology, 2018)
The choroid plexus (CP) compartment in the ventricles of the brain comprises fenestrated vasculature and, therefore, it is permeable to blood-borne mediators of inflammation. Here, we explored whether T-cell activation in the CP plays a role in regulating central nervous system (CNS) inflammation. We show that CD4 T cells injected into the lateral ventricles adhere to the CP, transmigrate across its epithelium, and undergo antigen-specific activation and proliferation. This process is enhanced following peripheral immune stimulation and significantly impacts the immune signaling induced by the CP. Ex vivo studies demonstrate that T-cell harboring the CP through its apical surface is a chemokine- and adhesion molecule-dependent process. We suggest that, within the CNS, the CP serves an immunological niche, which rapidly responds to peripheral inflammation and, thereby, promotes two-way T-cell trafficking that impact adaptive immunity in the CNS.